2009
DOI: 10.1002/eji.200838311
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐retroviral effects of type I IFN subtypes in vivo

Abstract: Type I IFN play a very important role in immunity against viral infections. Murine type I IFN belongs to a multigene family including 14 IFN-a subtypes but the biological functions of IFN-a subtypes in retroviral infections are unknown. We have used the Friend retrovirus model to determine the anti-viral effects of IFN-a subtypes in vitro and in vivo. IFN-a subtypes a1, a4, a6 or a9 suppressed Friend virus (FV) replication in vitro, but differed greatly in their anti-viral efficacy in vivo. Treatment of FV-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 59 publications
2
60
0
Order By: Relevance
“…By using a subgenomic genotype 2a replicon system, we observed high susceptibility of HCV for all subtypes with no distinction for IFN-␣17, which could be due to the different experimental setup and viral constructs. For herpes simplex virus (HSV), it was shown that the murine IFN-␣ homologs 1, 4, 5, 6, and 9 were inhibiting viral replication (37) and in a Friend virus in vivo infection model, therapeutic application with murine IFN-␣1, -4, -9, and -11 was able to reduce viral loads significantly in contrast to IFN-␣2, -5, and -6 (38,39). HEV replication could be efficiently blocked by ribavirin treatment and a significant benefit of a combination of any IFN-␣ subtype with ribavirin could not be observed using one constant ribavirin dose of 25 M (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By using a subgenomic genotype 2a replicon system, we observed high susceptibility of HCV for all subtypes with no distinction for IFN-␣17, which could be due to the different experimental setup and viral constructs. For herpes simplex virus (HSV), it was shown that the murine IFN-␣ homologs 1, 4, 5, 6, and 9 were inhibiting viral replication (37) and in a Friend virus in vivo infection model, therapeutic application with murine IFN-␣1, -4, -9, and -11 was able to reduce viral loads significantly in contrast to IFN-␣2, -5, and -6 (38,39). HEV replication could be efficiently blocked by ribavirin treatment and a significant benefit of a combination of any IFN-␣ subtype with ribavirin could not be observed using one constant ribavirin dose of 25 M (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, other IFN-a subtypes, such as 4 and 9, were also effective in reducing FV loads but did not increase absolute numbers of virus-specific CD8 + T cells (67). The most predominant IFN-a subtype that is produced after poly(I:C) treatment in vivo is IFN-a5 (data not shown), but the influence of this particular subtype on CD8 + T cell activity during FV infection has not been investigated so far.…”
Section: Cd8mentioning
confidence: 92%
“…Additionally, evolutionary selection of multiple functional IFN-␣ subtypes indicates that each subtype has essential and nonredundant functions (6). Evidence of this includes studies in the Friend retrovirus (FV) model, which showed that treatment with distinct IFN-␣ subtypes induced specific downstream responses that effectively controlled FV infections, whereas other subtypes induced responses that were ineffective (7,8). Furthermore, murine herpesvirus or influenza virus infections were controlled by different subtypes than those inhibiting FV (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%